Energy management systems in the industrial sector - Dreshpak, Nataliia (My University, 2024)
The article presents the problem of efficient electricity consumption in Ukrainian industry. The key reasons for the low efficiency of energy use in industry are explained. The structure of electricity consumption during 2019-2020 is analysed. The main problem for developing mining and metallurgical complex in Ukraine is determined
Системи енергетичного менеджменту в промисловому секторі
Keywords: mining and metallurgical complex of Ukraine; energy management systems; efficient electricity consumption; energy management